STRATEGI PEMULIHAN KESEHATAN MENTAL BAGI ANAK-ANAK KORBAN KEKERASAN - Pipin Windayani; Sadia Alaia; Teresia Putri Hepandari; Ema Nuraeningsih; Bintang Wigi P; Fitri Artnita (CV. ADIBA AISHA AMIRA, 2026)
Violence against children is a serious problem with long-term impacts on children's mental, emotional, and social health. Children who are victims of violence are at risk of experiencing psychological trauma, anxiety, depression, behavioral disorders, and obstacles to development and social functioning. This article aims to examine and analyze mental health recovery strategies for children who are victims of violence through a trauma-based approach and comprehensive environmental support. The method used is a literature review by examining various research results and scientific studies relevant to the mental health recovery of children who are victims of violence. The results of the study indicate that effective recovery requires a holistic approach that includes psychological interventions, family support, social support, and cross-sector collaboration such as child protection agencies, health workers, and law enforcement officials. The trauma healing approach has been proven to reduce psychological distress, increase feelings of security, and help children recover their self-confidence and social functioning. Furthermore, a supportive, safe, and child-friendly environment is an important factor in accelerating the recovery process. The conclusion of this study confirms that mental health recovery for children who are victims of violence cannot be carried out partially, but must be sustainable, integrated, and oriented towards the child's best interests to prevent the long-term impact of trauma and break the cycle of violence